Single and multi-frequency impedance characterization of symmetric activated carbon single capacitor cells - Suzana Sopčić; Davor Antonić; Zoran Mandić; Krešimir Kvastek; Višnja Horvat-Radošević (Journal of Electrochemical Science and Engineering, 2018)
Electrochemical impedance spectroscopy (EIS) technique is used for characterization of single cell symmetric capacitors having different mass loadings of activated carbon (AC). Relevant values of charge storage capacitance (CT) and internal resistance (ESR) were evaluated by the single frequency and multi-frequency analyses of measured impedance spectra. Curve fittings were based on the non-ideal R-C model that takes into account the parasitic inductance, contributions from electrode materials/contacts and the effects of AC porosity. Higher CT and lower ESR values were obtained not only for the cell with higher mass of AC, but also using the single vs. multi-frequency approach. Lower CT and higher values of ESR that are generally obtained using the multi-frequency method and curve fittings should be related to the not ideal capacitive response of porous AC material and too high frequency chosen in applying the single frequency analysis.